Facilitating Community-based Adaptation through Climate-Smart Agriculture - Trainer's Resource Book - International Institute of Rural Reconstruction (2021)
This training guide provides users with principles, concepts and practices on climate-smart agriculture (CSA) and community-based adaptation (CBA). It is composed of seven modules spread under a three-part document. This training guide was designed to enhance the capacity of users to facilitate processes leading to community-based adaptation to climate change, and to: • Understand the principles, concepts and practices related to climate change, CSA and CBA • Learn the application of participatory approaches and social learning processes in CBA • Identify strategies and techniques for implementing CSA approaches with farmers and fisherfolk; • Learn strategies and mechanisms for mainstreaming and sustaining CSA approaches; and • Develop action plans applicable to their areas of work